William Thomas Rawleigh papers - Rawleigh, William Thomas, 1870-1951.
Correspondence, financial records, lists, promotional material, charts, printed material, and other papers relating primarily to the 1924 presidential campaign of Robert M. La Follette. Subjects include the Progressive Republican League of Illinois and the W.T. Rawleigh Company. Correspondents include Hartwell L. Brunson, Herman Lewis Ekern, Fred L. Holmes, William Hugh Johnston, Charles J. MacGowan, John Mandt Nelson, and Oswald Garrison Villard.
Manufacturer and retailer of farm goods, chairman of the La Follette for President Committee, and Robert M. La Follette's campaign treasurer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brunson, Hartwell L. -- Correspondence; Ekern, Herman Lewis, -- 1872-1954 -- Correspondence; Holmes, Fred L., -- 1883-1946 -- Correspondence; Johnston, William Hugh, -- 1874-1937 -- Correspondence; La Follette, Robert M. -- 1855-1925.; MacGowan, Charles J. -- Correspondence; Nelson, John Mandt, -- 1870-1955 -- Correspondence; Villard, Oswald Garrison, -- 1872-1949 -- Correspondence; Progressive Republican League of Illinois; W.T. Rawleigh Company; Presidents -- United States -- Election -- 1924.; Progressivism (United States politics); United States -- Politics and government -- 1901-1953.; Campaign managers; Manufacturers; Merchants